COVID-19 and combat sports: to fight or not to fight? - Sethi, N. K. (British Journal of Sports Medicine, 2020)
Governments are now turning to the complex question of how and when to open different states and countries to business and normal life. For combat sports to resume this summer we should explore the possibility of initially holding events "behind closed doors".